The survivor - Mills, Kyle, 1966-; Flynn, Vince (New York : Emily Bestler Books/Atria, 2015)
When a former CIA agent steals classified information and offers it to the Pakistani secret forces, Mitch Rapp must prevent the information from falling into the wrong hands.
Keywords: Rapp, Mitch (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Terrorism -- Prevention -- Fiction; Suspense fiction